The Effect of the Physical Environment on Consumer Impressions in Contemporary Coffee Shops in Medan City - Winata, Edi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of the physical environment consisting of ambience, layout and aesthetic facility on consumer impressions at contemporary coffee shops in Medan City. The method used in this study using Multiple Linear Regression with a total of respondents 90 students of STIM Sukma. The results of the study show that there is a positive and significant relationship in the physical environment to the impression on coffee shop consumers in Medan City.The results show that partially ambience has a positive and significant effect on consumer impressions, but layout and aesthetics have no effect on consumer impressions at Contenporary Coffee Shops in Medan City. Simultaneously, ambience, layout and aesthetics have a significant effect on Contemporary Coffee Shop. The adjusted R square value of this research model is 0.276 (27.60%)